Whole-genome Analysis Reveals Contrasting Relationships Among Nuclear and Mitochondrial Genomes Between Three Sympatric Bat Species - Laine Veronika N; Sävilammi Tiina; Wahlberg Niklas; Meramo Katarina; Ossa Gonzalo; Johnson Joseph S; Blomberg Anna S; Yeszhanov Aidyn B; Yung Veronica; Paterson Steve; Lilley Thomas M (OXFORD UNIV PRESS, 2025)
Understanding mechanisms involved in speciation can be challenging, especially when hybridization or introgression blurs species boundaries. In bats, resolving relationships of some closely related groups has proved difficult due subtle interspecific variation both in morphometrics and molecular data sets. The endemic South American Histiotus bats, currently considered a subgenus of Eptesicus, harbor unresolved phylogenetic relationships and of those is a trio consisting of two closely related species: Eptesicus (Histiotus) macrotus and Eptesicus (Histiotus) montanus, and their relationship with a third, Eptesicus (Histiotus) magellanicus. The three sympatric species bear marked resemblance to each other, but can be differentiated morphologically. Furthermore, previous studies have been unable to differentiate the species from each other at a molecular level. In order to disentangle the phylogenetic relationships of these species, we examined the differentiation patterns and evolutionary history of the three Eptesicus (H.) species at the whole-genome level. The nuclear DNA statistics between the species suggest strong gene flow and recent hybridization between E. (H.) montanus and E. (H.) macrotus, whereas E. (H.) magellanicus shows a higher degree of isolation. In contrast, mitochondrial DNA shows a closer relationship between E. (H.) magellanicus and E. (H.) montanus. Opposing patterns in mtDNA and nuclear markers are often due to differences in dispersal, and here it could be both as a result of isolation in refugia during the last glacial maximum and female philopatry and male-biased dispersal. In conclusion, this study shows the importance of both the nuclear and mitochondrial DNA in resolving phylogenetic relationships and species histories.